PsycEXTRA Dataset 1982
DOI: 10.1037/e447592004-001
|View full text |Cite
|
Sign up to set email alerts
|

Count me in: Academic achievement and social outcomes of mainstreaming students with mild academic handicaps.

Abstract: The paper reviews research on the effects of placement in full-time special education classes, part-time regular classes with resource support, and full-time regular classes on mildly handicapped students. Also examined are programs designed to improve achievement, social-emotional adjustment, and social acceptance of the academically handicapped by their nonhandicapped peers. Studies of placements indicate no consistent benefits of full-time special education on any major outcomes; the research tells to favor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…Although a number of recent reviews provides evidence in support of mainstreaming (Carlberg & Kavale, 1980;Madden & Slavin, 1982;Leinhardt & Palley, 1982;Semmel et al, 1979), their positive findings for the most part reflect only academic outcomes for mainstreamed disabled students. The data from such reviews also tend to suggest that mainstreaming is effective only for students with certain special education classifications.…”
Section: Conclusion and Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Although a number of recent reviews provides evidence in support of mainstreaming (Carlberg & Kavale, 1980;Madden & Slavin, 1982;Leinhardt & Palley, 1982;Semmel et al, 1979), their positive findings for the most part reflect only academic outcomes for mainstreamed disabled students. The data from such reviews also tend to suggest that mainstreaming is effective only for students with certain special education classifications.…”
Section: Conclusion and Discussionmentioning
confidence: 87%
“…Similarly, Leinhardt and Palley (1982) concluded that placement of special education students in regular classes was more effective for high-IQ students and that placement in special education classes was more facilitative of the academic performance of low-IQ, educable mentally retarded students. In terms of the social outcomes of mainstreaming, findings from other studies generally indicate a negative impact (Heller, 1981;Meyers et al, 1980;Madden & Slavin, 1982).…”
Section: Conclusion and Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Researchers have noted that there are social and academic benefits of inclusive education for both the children with disabilities and their typically developing peers (Halvorsen & Sailor, 1990; Hunt & Goetz, 1997; Madden & Slavin, 1982; Peltier, 1997; Tapasak & Walther-Thomas, 1999). What is a little disconcerting in this current study is the perceived differences in the benefits for the two groups of children.…”
Section: Discussionmentioning
confidence: 99%
“…The implied perception of the initial public laws was that the purpose of mainstreaming was for the social benefit of the students with disabilities yet the promotion of partial or full inclusion seems more all encompassing. Benefits of inclusive education may be both social and academic (Hunt & Goetz, 1997; Madden & Slavin, 1982) and can exist for the students with disabilities as well as for their typically developing peers (Peltier, 1997; Tapasak & Walther-Thomas, 1999).…”
mentioning
confidence: 99%